Hard carbon composite material and preparation method and application thereof

By using hard carbon composite materials in lithium-ion battery anode materials and using the physical adsorption layer of lithium phosphate to improve the specific capacity and cycle stability of the material, the problem of lithium precipitation in existing graphite materials at fast charging and low temperature is solved, achieving Higher energy density and battery safety.

CN119340370APending Publication Date: 2025-01-21UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202411529227.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material graphite is prone to lithium extraction in the case of fast charging and low-temperature use, resulting in safety problems such as battery circulation performance attenuation and thermal runaway, and its theoretical specific capacity is not enough to meet modern energy density requirements.

Method used

The hard carbon composite material is used as the negative electrode material of the lithium -ion battery, and the hard carbon is the core. The lithium phosphate is evenly scattered on the hard carbon surface by physical adsorption to form particles of the core shell structure to improve the capacity and cycle stability of the material.

Benefits of technology

It improves the first Coulomb efficiency, rate performance and cycle stability of lithium-ion batteries, reduces the occurrence of electrolyte decomposition and side reactions, enhances the stability and safety of the battery, and at the same time increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340370A_ABST
    Figure CN119340370A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon composite material, the hard carbon composite material is a particle with a core-shell structure, the interior of the core-shell structure is hard carbon, the exterior of the core-shell structure is lithium phosphate, and the lithium phosphate is dispersed on the surface of the hard carbon in a physical adsorption manner. On the other hand, the invention provides a preparation method of the hard carbon composite material, and the preparation method comprises the following steps: in an inert atmosphere, mixing hard carbon, a phosphating reagent and a lithium salt, and carrying out uniform ball milling to obtain a precursor mixture; and sintering the precursor mixture in an inert atmosphere to obtain the hard carbon composite material. On the other hand, the invention provides application of the hard carbon composite material in the lithium ion battery, and the hard carbon composite material is used as a negative electrode of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hard carbon negative electrode materials, and in particular relates to a hard carbon composite material and a preparation method and application thereof. Background Art

[0002] As the mainstream energy storage device, lithium-ion batteries are widely used in electric vehicles and 3C digital devices. As the main component of lithium-ion batteries, negative electrode materials greatly determine the performance of lithium-ion batteries. In related technologies, the negative electrode materials of lithium-ion batteries used commercially are mostly graphite. As a negative electrode material of lithium-ion batteries, graphite has a low voltage lithium insertion platform capacity and high coulombic efficiency and cycle stability. However, its low theoretical specific capacity (372mAh g -1 ) cannot meet the current demand for energy density. Under fast charging and low-temperature usage scenarios, commercial graphite negative electrodes are prone to lithium deposition due to huge structural changes and polarization effects, causing safety issues such as battery cycle performance degradation and thermal runaway.

[0003] Compared with graphite, the short-range ordered and long-range disordered structural characteristics of hard carbon are conducive to the rapid transfer of lithium ions. At the same time, compared with graphite, the structural characteristics of hard carbon materials with larger interlayer spacing, more pores and defect structures make it not only have a higher specific capacity, but also have excellent low-temperature charge and discharge capabilities and rate performance. In the relevant technology, the hard carbon prepared by modification by heteroatom doping and activation pore formation often has a larger specific surface area, a lower degree of graphitization and a higher defect content. This hard carbon mainly stores lithium ions by adsorption, and the charge and discharge curve only shows a slope capacity without a clear platform capacity, which inevitably reduces the energy density of the whole battery, so its application has been limited. At the same time, a large amount of electrolyte decomposes to produce a solid electrolyte interface membrane (SEI) enriched with organic matter, which reduces the first coulomb efficiency of the hard carbon negative electrode, which is not conducive to the charge transfer of lithium ions and the cycle stability of the hard carbon negative electrode under fast charging environment.

[0004] Therefore, developing a hard carbon anode material with higher coulombic efficiency and energy density has far-reaching practical significance. Summary of the invention

[0005] In view of this, in order to at least partially solve at least one of the technical problems mentioned above, the present disclosure provides a hard carbon composite material, which is a core-shell structured particle, the interior of the core-shell structure is hard carbon, and the exterior of the core-shell structure is lithium phosphate, wherein the lithium phosphate is dispersed on the surface of the hard carbon by physical adsorption.

[0006] According to an embodiment of the present disclosure, the mass fraction of lithium phosphate is 0.1-10wt%.

[0007] According to an embodiment of the present disclosure, the particle size of lithium phosphate is less than 100 nm, and the particle size of hard carbon is 5-15 μm.

[0008] In another aspect of the present disclosure, there is provided a method for preparing the aforementioned hard carbon composite material, comprising:

[0009] In an inert atmosphere, hard carbon, a phosphating agent and a lithium salt are mixed and ball-milled to obtain a precursor mixture;

[0010] The precursor mixture is sintered in an inert atmosphere to obtain a hard carbon composite material.

[0011] According to an embodiment of the present disclosure, in the sintering process, the sintering temperature is 600-1000° C., and the sintering time is 1-10 h.

[0012] According to an embodiment of the present disclosure, during the sintering process, the heating rate is 1-10° C. / min.

[0013] According to an embodiment of the present disclosure, the phosphating agent includes at least one of ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid; the lithium salt includes at least one of lithium hydroxide and lithium oxide.

[0014] According to an embodiment of the present disclosure, the mass fraction of the phosphating agent is 0.08-8wt%.

[0015] According to an embodiment of the present disclosure, the mass fraction of the lithium salt is 0.02-2wt%.

[0016] In another aspect of the present disclosure, there is provided a use of the aforementioned hard carbon composite material in a lithium ion battery, wherein the hard carbon composite material serves as a negative electrode of the lithium ion battery.

[0017] According to the embodiments of the present disclosure, hard carbon as the core has a high specific capacity and good cycle stability, and is one of the ideal choices for negative electrode materials of lithium-ion batteries. The microcrystalline structure of hard carbon not only provides more lithium storage sites, but also facilitates the rapid embedding and de-embedding of lithium ions. At the same time, lithium phosphate is evenly dispersed on the surface of hard carbon by physical adsorption to form a protective layer. This structure can effectively prevent direct contact between hard carbon and electrolyte, reduce the occurrence of side reactions, and improve the stability and safety of the battery. When the hard carbon composite material proposed in the present disclosure is applied to the negative electrode of a lithium-ion battery, lithium phosphate is coated on the surface of hard carbon particles in the form of physical adsorption, on the one hand, a solid electrolyte interface enriched with lithium phosphate is formed, and on the other hand, lithium phosphate, as a fast ion conductor of lithium ions, can improve the first coulombic efficiency, rate performance and cycle stability of lithium-ion batteries. A more stable interface structure can be formed between the solid electrolyte interface enriched with inorganic components and the hard carbon material, reducing the interface resistance and the occurrence of interface side reactions, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a scanning electron microscope image of the hard carbon composite material prepared in the embodiment of the present disclosure;

[0019] Figure 2 is a scanning electron microscope image of the hard carbon material prepared in the comparative example of the present disclosure;

[0020] Figure 3 is a first charge and discharge curve diagram of the hard carbon composite material prepared in the embodiment of the present disclosure;

[0021] Figure 4 is the first charge and discharge curve of the hard carbon material prepared in the comparative example of the present disclosure;

[0022] Figure 5 It is a comparison chart of the rate performance of the hard carbon materials of the embodiments of the present disclosure and the comparative examples as negative electrode materials for lithium-ion batteries. DETAILED DESCRIPTION

[0023] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0024] The endpoints and any values ​​of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.

[0025] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.

[0026] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0027] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present disclosure shall have the usual meanings understood by persons with ordinary skills in the field to which the present disclosure belongs. If the full text involves descriptions such as "first", "second", etc., the descriptions such as "first", "second", etc. are only used to distinguish similar objects, and cannot be understood as indicating or implying their relative importance, order of precedence, or implicitly indicating the number of technical features indicated. It should be understood that the data described by "first", "second", etc. can be interchangeable under appropriate circumstances.

[0028] In order to make the purpose, technical solution and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of them.

[0029] Similarly, in order to simplify the present disclosure and help understand one or more of the various disclosed aspects, in the above description of the exemplary embodiments of the present disclosure, the various features of the present disclosure are sometimes grouped together into a single embodiment, figure, or description thereof. The description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" and the like means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present disclosure. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0030] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this disclosure.

[0031] During the implementation of the present invention, it was found that in order to solve the problem of low initial coulombic efficiency and enrichment of organic components at the solid electrolyte interface caused by large-scale decomposition of the electrolyte during the first discharge of the hard carbon negative electrode, the present invention adopts a strategy of forming a coating layer on the hard carbon surface with inorganic substances, so that lithium phosphate is coated on the surface of the hard carbon particles in the form of physical adsorption, forming a solid electrolyte interface enriched with lithium phosphate.

[0032] The present disclosure provides a hard carbon composite material. The hard carbon composite material is a particle of a core-shell structure. The interior of the core-shell structure is hard carbon, and the exterior of the core-shell structure is lithium phosphate, wherein the lithium phosphate is dispersed on the surface of the hard carbon by physical adsorption.

[0033] According to the embodiments of the present disclosure, hard carbon as the core has a high specific capacity and good cycle stability, and is one of the ideal choices for negative electrode materials of lithium-ion batteries. The microcrystalline structure of hard carbon not only provides more lithium storage sites, but also facilitates the rapid embedding and de-embedding of lithium ions. At the same time, lithium phosphate is evenly dispersed on the surface of hard carbon by physical adsorption to form a protective layer. This structure can effectively prevent direct contact between hard carbon and electrolyte, reduce the occurrence of side reactions, and improve the stability and safety of the battery. When the hard carbon composite material proposed in the present disclosure is applied to the negative electrode of a lithium-ion battery, lithium phosphate is coated on the surface of hard carbon particles in the form of physical adsorption, on the one hand, a solid electrolyte interface enriched with lithium phosphate is formed, and on the other hand, lithium phosphate, as a fast ion conductor of lithium ions, can improve the first coulombic efficiency, rate performance and cycle stability of lithium-ion batteries. A more stable interface structure can be formed between the solid electrolyte interface enriched with inorganic components and the hard carbon material, reducing the interface resistance and the occurrence of interface side reactions, thereby improving the cycle performance of the battery.

[0034] According to an embodiment of the present disclosure, the mass fraction of lithium phosphate is 0.1-10wt%, for example, it can be 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc.

[0035] According to the embodiments of the present disclosure, the mass fraction of lithium phosphate in the range of 0.1-10wt% can ensure that the lithium phosphate is evenly distributed on the surface of the hard carbon particles and that the lithium phosphate does not agglomerate.

[0036] According to an embodiment of the present disclosure, the particle size of lithium phosphate is less than 100 nm, and the particle size of hard carbon is 5-15 μm.

[0037] In another aspect of the present disclosure, a method for preparing the aforementioned hard carbon composite material is provided, comprising the following steps S1 and S2:

[0038] Step S1: In an inert atmosphere, hard carbon, a phosphating agent and a lithium salt are mixed and ball-milled to obtain a precursor mixture;

[0039] Step S2: Sintering the precursor mixture in an inert atmosphere to obtain a hard carbon composite material.

[0040] According to the embodiments of the present disclosure, the present disclosure uses a simple thermochemical method to make lithium phosphate interact with the surface of the hard carbon material through a sintering reaction, thereby forming a physically adsorbed lithium phosphate coating layer on the hard carbon surface, and obtaining a hard carbon composite material of lithium phosphate coated hard carbon. The method has the advantages of simple process and easy control. By directly mixing hard carbon, phosphating agent and lithium salt, these raw materials can contact and react with each other more evenly during the sintering process. This uniform mixing helps the lithium phosphate layer to form a uniform coating layer on the hard carbon surface, thereby improving the overall performance of the material; the mixing reaction allows the reaction process and the properties of the product to be precisely controlled by adjusting parameters such as the ratio of raw materials, sintering temperature and time. This controllability helps to optimize the thickness, structure and composition of the lithium phosphate coating layer to meet specific performance requirements. If lithium phosphate is used directly for coating, the coating layer may be uneven due to the uneven size, shape and distribution of lithium phosphate particles. This unevenness will affect the overall performance of the hard carbon composite material.

[0041] According to an embodiment of the present disclosure, in the sintering process, the sintering temperature is 600-1000°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and the sintering time is 1-10h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0042] According to the embodiments of the present disclosure, when the sintering temperature is lower than 600°C, it is difficult to form lithium phosphate, and it is difficult to form physical adsorption between lithium phosphate and hard carbon particles; when the sintering temperature is higher than 1000°C, the hard carbon particles may undergo graphite phase changes, changing the hard carbon microstructure.

[0043] According to an embodiment of the present disclosure, in the sintering process, the heating rate is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.

[0044] According to an embodiment of the present disclosure, the phosphating agent includes at least one of ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid; the lithium salt includes at least one of lithium hydroxide and lithium oxide.

[0045] According to an embodiment of the present disclosure, the mass fraction of the phosphating agent is 0.08-8wt%, for example, it can be 0.08wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, etc.

[0046] According to an embodiment of the present disclosure, the mass fraction of the lithium salt is 0.02-2wt%, for example, it can be 0.02wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, etc.

[0047] In another aspect of the present disclosure, there is provided a use of the aforementioned hard carbon composite material in a lithium ion battery, wherein the hard carbon composite material serves as a negative electrode of the lithium ion battery.

[0048] According to the embodiments of the present disclosure, when the hard carbon composite material is used as the negative electrode of a lithium-ion battery, lithium phosphate can provide a fast transmission channel for lithium ions, allowing the ions to diffuse quickly into the interior of the electrode. At the same time, the coating on the hard carbon surface can also reduce the large-scale decomposition of the electrolyte, forming a solid electrolyte interface enriched with lithium phosphate. The presence of the lithium phosphate protective layer also greatly improves the safety performance of lithium-ion batteries and reduces the safety hazards caused by electrolyte leakage or lithium dendrite growth. Compared with uncoated hard carbon materials, negative electrode materials coated with lithium phosphate can achieve higher coulombic efficiency, improve the charge transfer ability and cycle stability of the hard carbon negative electrode, and the rate performance and cycle stability of lithium-ion batteries.

[0049] It should be noted that the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, other embodiments obtained by ordinary technicians in the field without creative work are all within the scope of protection of the present disclosure.

[0050] Example

[0051] 114 mg of ammonium hydrogen phosphate and 62 mg of lithium hydroxide precursor (molar mass ratio of 1:2) and 2 g of hard carbon (the hard carbon material is commercially available Kuraray hard carbon) are added into the cavity of the ball mill, introduced into an argon atmosphere, ball milled, and mixed evenly to obtain a precursor mixture. Among them, the mass ratio of hard carbon to phosphating agent and lithium source is: 100:5.7:3.1;

[0052] The hard carbon composite material coated with lithium phosphate was obtained by calcining at 900°C for 6 hours in an argon atmosphere.

[0053] Comparative Example

[0054] Take a hard carbon sample (the hard carbon material is Kuraray hard carbon purchased on the market).

[0055] The hard carbon material prepared in Example 1 and Comparative Example 1 was mixed with a conductive agent and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone was added to stir the mixture evenly; the mixed slurry was evenly coated on a copper foil and vacuum dried as a negative electrode. Lithium foil was used as the counter electrode, and 1M LiPF was used as the electrolyte. 6 The mixture of propylene carbonate (PC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1, and the separator is a PP film, assembled into a button cell. The charge and discharge test was carried out by the Blue Electric Battery Test System, and the voltage range was 0.001-2V.

[0056] Test Case

[0057] The hard carbon composite material prepared in the example and the hard carbon material prepared in the comparative example were subjected to morphology tests.

[0058] Figure 1 , Figure 2 The figures are scanning electron microscope images of the hard carbon composite material and the hard carbon material prepared in the examples and comparative examples of the present disclosure, respectively.

[0059] like Figure 1 , 2 As shown, many nanometer-scale lithium phosphate particles are embedded on the surface of the lithium phosphate-coated hard carbon composite material prepared in the embodiment of the present disclosure, verifying that the hard carbon composite material proposed in the present disclosure is coated with lithium phosphate on the outside.

[0060] The hard carbon materials prepared in the examples and comparative examples were subjected to relevant electrochemical performance tests, and the results are shown in Table 1.

[0061] Table 1

[0062]

[0063] It can be seen from the data in Table 1 that the lithium phosphate coated negative electrode material in the embodiment has a higher coulombic efficiency and excellent rate performance, can exert a higher reversible capacity at a higher current density, and the cycle stability is also significantly improved.

[0064] Figure 3 , Figure 4 They are respectively the first charge and discharge curves of the hard carbon composite material prepared in the embodiment of the present disclosure and the hard carbon material prepared in the comparative example. Figure 5 It is a comparison chart of the rate performance of the hard carbon materials of the embodiments of the present disclosure and the comparative examples as negative electrode materials for lithium-ion batteries.

[0065] like Figure 3 , Figure 4As shown, the hard carbon composite material proposed in the present disclosure has a higher initial coulomb efficiency (ICE) than conventional hard carbon materials. Under the same test conditions, the initial coulomb efficiency of a lithium-ion battery using the hard carbon composite material prepared in the embodiment of the present application as the negative electrode is 70%, while the initial coulomb efficiency of a lithium-ion battery using conventional hard carbon as the negative electrode in the comparative example is 55%. It can be seen that the lithium phosphate coating can improve the conductivity of the hard carbon material to a certain extent and improve the initial coulomb efficiency of the lithium-ion battery. Figure 5 As shown, in the cycle test, the hard carbon composite material proposed in the present invention has better cycle stability than conventional hard carbon materials, and has a larger discharge specific capacity and charge and discharge efficiency, which verifies that a more stable interface structure can be formed between the solid electrolyte interface enriched with lithium phosphate inorganic components and the hard carbon material, reducing the interface resistance and the occurrence of interface side reactions, thereby improving the cycle performance of the battery.

[0066] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A hard carbon composite material, characterized in that: The hard carbon composite material is a particle of a core-shell structure, wherein the interior of the core-shell structure is hard carbon and the exterior of the core-shell structure is lithium phosphate, wherein the lithium phosphate is dispersed on the surface of the hard carbon by physical adsorption.

2. The hard carbon composite material according to claim 1, wherein The mass fraction of the lithium phosphate is 0.1-10wt%.

3. The hard carbon composite material according to claim 1, wherein The particle size of the lithium phosphate is less than 100 nm, and the particle size of the hard carbon is 5-15 μm.

4. A method for preparing the hard carbon composite material according to any one of claims 1 to 3, comprising: In an inert atmosphere, hard carbon, a phosphating agent and a lithium salt are mixed and ball-milled to obtain a precursor mixture; The precursor mixture is sintered in an inert atmosphere to obtain a hard carbon composite material.

5. The preparation method according to claim 4, wherein: In the sintering process, the sintering temperature is 600-1000° C. and the sintering time is 1-10 hours.

6. The preparation method according to claim 5, wherein: In the sintering process, the heating rate is 1-10°C / min.

7. The preparation method according to claim 4, wherein The phosphating agent includes at least one of ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid; The lithium salt includes at least one of lithium hydroxide and lithium oxide.

8. The preparation method according to claim 4, wherein The mass fraction of the phosphating agent is 0.08-8wt%.

9. The preparation method according to claim 4, wherein: The mass fraction of the lithium salt is 0.02-2wt%.

10. Use of the hard carbon composite material according to any one of claims 1 to 3 in a lithium ion battery, wherein: The hard carbon composite material is used as the negative electrode of a lithium ion battery.

Citation Information

Patent Citations

  • Method for removing lithium ion battery nickel-rich material surface lithium residues by liquid phase precipitation method

    CN102881911A

  • Lithium phosphate coated sulfur / carbon composite material as well as preparation method and application thereof

    CN110061218A

  • Lithium phosphate coated lithium ion battery high-nickel positive electrode material and preparation method thereof

    CN113328069A

  • Negative electrode material capable of being charged at low temperature and preparation method thereof

    CN113422026A

  • Silicon-based composite material containing lithium phosphate coating layer constructed by in-situ conversion and preparation method of silicon-based composite material

    CN113422037A

Cited By

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN119994038A